The Benson murder case - Van Dine, S. S., 1888-1939; Stoops, Herbert Morton, 1887-1948 (Salt Lake City, UT : Project Gutenberg, 2023)
"The Benson murder case" by S. S. Van Dine is a mystery novel published in 1926. When a New York man-about-town is found dead under mysterious circumstances, amateur detective Philo Vance offers his psychological insights to assist District Attorney Markham's investigation. Using careful observation and deduction, Vance reconstructs the crime and determines specific physical characteristics of the killer. He methodically examines the victim's business associates and romantic connections, working to break through alibis and uncover the truth behind this locked-room mystery. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_Benson_Murder_Case
Release date is 2023-04-23
Transcribed and produced by Brian Raiter
Keywords: Detective and mystery stories; Murder -- Investigation -- Fiction; Manhattan (New York, N.Y.) -- Fiction; Stockbrokers -- Fiction; Vance, Philo (Fictitious character) -- Fiction; Private investigators -- New York (State) -- New York -- Fiction